1996
DOI: 10.1159/000292268
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fibrin Sealant for Reproductive Surgery: A Randomized Study in the Rabbit Model

Abstract: The present study was undertaken to compare adhesion formation and reproductive outcome after reproductive surgery with or without the application of fibrin sealant. At laparotomy, the ovaries and uterine horns of 20 rabbits were longitudinally incised on the antimesenteric side using a monopolar microneedle. At random, one ovary and the ipsilateral uterine horn were covered with fibrin sealant, while those on the contralateral side were left uncovered without application of sutures. The rabbits were then mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…25 Many experimental studies have shown that fibrin glue cannot prevent abdominal adhesions sufficiently. [26][27][28] However, some authors have described its efficacy in preventing adhesion. 29-31 These discrepancies may be due to the use of different experimental conditions, such as fibrinogen concentration (gel mechanics and hydration), as well as fibrin gel barrier thickness.…”
Section: Discussionmentioning
confidence: 99%
“…25 Many experimental studies have shown that fibrin glue cannot prevent abdominal adhesions sufficiently. [26][27][28] However, some authors have described its efficacy in preventing adhesion. 29-31 These discrepancies may be due to the use of different experimental conditions, such as fibrinogen concentration (gel mechanics and hydration), as well as fibrin gel barrier thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Using in vivo systems, these biologic effects of Tisseel and derivative fibrin sealant formulations of these experiments would be complemented by its ability to achieve hemostasis, thereby limiting collection of blood clots, which have been implicated in adhesion development. Consistent with the hypothesis that Tisseel would be expected to reduce adhesions are extensive studies in multiple animal species and in humans, utilizing a diverse variety of surgical models including cardiac, bowel, reproductive tract, and tendons 15–33 . However, whether removal of aprotinin from Tisseel would further improve its in vivo efficacy to reduce adhesions remains to be established.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with the hypothesis that Tisseel would be expected to reduce adhesions are extensive studies in multiple animal species and in humans, utilizing a diverse variety of surgical models including cardiac, bowel, reproductive tract, and tendons. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] However, whether removal of aprotinin from Tisseel would further improve its in vivo efficacy to reduce adhesions remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy remains on the effect of thrombin and fibrin sealant on adhesion formation. While some studies report more extensive adhesion formation with the use of fibrin sealant (Gauwerky et al, 1990), others demonstrate no increase (McGaw et al, 1988;Bruel et al, 1993;Bilgin et al, 1995;Evrard et al, 1996;Marana et al, 1996) and even a reduction (Lindenberg et al, 1985;de Virgilio et al, 1990;Tulandi, 1991;Caballero and Tulandi, 1992;Sheppard et al, 1993;De Iaco et al, 1994;Takeuchi et al, 1996). The diversity of results may be due to differences in study design, injury model, control group, chemical composition and mode of application of the fibrin sealant and evaluation of adhesions.…”
mentioning
confidence: 99%